A study on relationship between compensation and job satisfaction among employees / Nurul Atasha Abu Bakar - Abu Bakar, Nurul Atasha (2014)
The objective of this study is to examine the relationship between compensation and job satisfaction among employees. This study has been examined by three types of compensation which are salary, reward and flexible working hour. One of the objectives is also to identify which of the compensation factors are most highly influence employees' satisfaction. Hence, the study is to examine the satisfaction among employees towards the compensations given to them and which of these compensations are the most satisfied to the employee. The study was carried out in a government-linked company in Seberang Perai, Pulau Pinang. A total of 84 questionnaires were returned from 120 questionnaires distributed to the respondents in the organization and simple random sampling had been used as the sampling method.